Development and evaluation of ibuprofen-loaded chitosan nanoparticles for pulmonary therapy - Olvera Rodríguez, I.; Mora-Muñoz, J. M.; Pérez, V.; Campos-Guillén, J.; Gallegos-Reyes, M. A.; García-Solís, P.; Álvarez López, A.; Vallejo Becerra, V.; Rodríguez-Morales, J. A.; Rodríguez-Méndez, A. J.; Guzmán Martínez, C. (Frontiers in Nanotechnology, 2024)
Lung injuries are widespread nowadays due to numerous lung diseases that lead to moderate to severe alveolar damage. The latter can lead to respiratory system disorders that can be mild, permanent, or fatal. This article presents a new approach that utilizes the incubation method to obtain nanoencapsulated ibuprofen in a chitosan matrix for pulmonary therapy. It highlights the controlled release of the drug for targeted delivery to the lung and emphasizes its role in reducing inflammation and promoting alveolar regeneration. The study demonstrates the successful encapsulation of ibuprofen without altering the molecular structure of chitosan and highlights the optimal dose for therapeutic benefit. The results suggest, considering lung tissue cell viability and histological analysis, that 500 mg doses of ibuprofen have the potential to treat lung injury and highlight the importance of dose optimization.In conclusion, this research presents a promising approach to pulmonary medicine, leveraging the synergistic effects of ibuprofen and chitosan in a nanoencapsulated form to enhance treatment efficacy and safety.